1993
DOI: 10.1002/ajmg.1320470615
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to quantitative lipoprotein traits associated with coronary artery disease: Analysis of a large pedigree from the Bogalusa heart study

Abstract: A pedigree of a large family with high prevalence of heart disease is subjected to association and sib-pair linkage analysis to investigate the role of 5 candidate genes in the regulation of lipoprotein metabolism and the development of coronary artery disease. At the 5% nominal significance level, the apolipoprotein B locus (APOB) was found to be linked to high-density lipoprotein cholesterol level (HDL-C), low-density lipoprotein cholesterol level (LDL-C), the ratio HDL-C/LDL-C, and apolipoprotein AI level t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…A linkage study of data from the Framingham Study families 39 reported nominal evidence for QTLs, influencing log TG levels (LODϭ1.5) and log TG/ HDL (LODϭ1.1) within 10 cM of the markers nearest the multipoint peak in our analyses. Penetrance-model-based linkage analyses of data from the Bogalusa Heart Study 22 and a study by Heiba et al 40 yielded nominal evidence for linkage (LODϭ1.7 and PϽ0.05, respectively) between a QTL for HDL-C levels and a haptoglobin locus marker situated within 5 cM of the marker loci nearest our multipoint peak. In contrast, MacPherson et al 41 found no evidence for a QTL for plasma HDL-C levels linked to the CETP locus in their study of data from 104 nuclear families.…”
Section: Discussionmentioning
confidence: 59%
“…A linkage study of data from the Framingham Study families 39 reported nominal evidence for QTLs, influencing log TG levels (LODϭ1.5) and log TG/ HDL (LODϭ1.1) within 10 cM of the markers nearest the multipoint peak in our analyses. Penetrance-model-based linkage analyses of data from the Bogalusa Heart Study 22 and a study by Heiba et al 40 yielded nominal evidence for linkage (LODϭ1.7 and PϽ0.05, respectively) between a QTL for HDL-C levels and a haptoglobin locus marker situated within 5 cM of the marker loci nearest our multipoint peak. In contrast, MacPherson et al 41 found no evidence for a QTL for plasma HDL-C levels linked to the CETP locus in their study of data from 104 nuclear families.…”
Section: Discussionmentioning
confidence: 59%
“…As with I405V, the Taq1B studies were subjected to a formal meta-analysis as described above. Data were excluded if they reported data on subjects specifically selected by abnormal lipid criteria (68,69,77,83,88,107), on alcoholics (75), on related individuals (91), and specifically on patients with non-CAD related disease (76,78). Duplicate publications and publications with patient overlap were excluded.…”
Section: Wild-type Proteinmentioning
confidence: 99%
“…The Bogalusa heart studies [30][31][32][33] have presented a considerable body of evidence on the genetic and epidemiological dynamics of lipids and apolipoprotein concentrations as they relate to the risk of CHD across races and genders, but have no endpoint data as yet. The few studies that have examined the association of hyperlipidaemia with CHD in minorities have shown that total cholesterol was a predictor of CHD risk.…”
Section: Agt235 Polymorphism and Cad Riskmentioning
confidence: 99%